Elucidation of Sonochemical Reaction Kinetics of Biodiesel Production from Jatropha Oil - Valerian Victor, Kong (2012)
Biodiesel, an alternative renewable fuel made from transesterification of vegetable oil with alcohol, is becoming more readily available for use in blends with conventional diesel fuel for transportation applications. One way of reducing the biodiesel production costs is to use the less expensive feedstock containing fatty acids such as inedible oils, animal fats, waste food oil and by products of the refining vegetables oils. Biodiesel production process is the transesterification of the used two-steps catalyzed process with jatropha oil and methanol, in the presence of alkali catalyst, to yield the ethyl ester as a product and glycerine as a by-product. In the acid treatment or the acid-catalyzed esterification, the temperature is set at 60°C, acid catalyst of 1% w/w H2SO4. These studies have been performed based on 2 effects, temperature and oil to methanol molar ratio with fixed parameter of 1% w/w NaOH and 20 kHz of frequency for optimization and lastly with time which is used for kinetic study. As a result, the best condition that has been determined for maximum biodiesel production was 1:6 of oil to methanol molar ratio. However, the temperature does not effect to the biodiesel yield. Biodiesel yield in biodiesel production from jatropha curcas oil were measured by using 1H NMR spectrometer analysis. These processes which using ultrasonic reactor is easy and faster than other biodiesel production process because cavities caused by the ultrasound at the catalyst surface increase the catalyst activity and reduce the activation over potential loss.